Enhancing Patient Loyalty Through Operational Strategies and Service Quality: The Impact of Patient Satisfaction on Company Revenue - Renaldus Iwan Sumarta; Maun Jamaludin; Iman Sudirman (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Hospitals, as public companies, must prioritize not only healthcare quality but also revenue and sustainability. Patient satisfaction serves as a key indicator of service quality, while effective operational strategies and high service quality are essential for fostering patient loyalty.Purpose: This study analyzes how operational strategies and service quality influence patient loyalty and, consequently, company revenue.Design/Methodology/Approach: A quantitative research methodology was employed, utilizing simple random sampling to collect data from 187 patients in private hospitals in Bandung. Data were gathered through questionnaires on a 7-point Likert scale, complemented by interviews. SmartPLS 4.0 software was used for data analysis.Finding/Result: The findings reveal that operational strategies significantly enhance service quality and patient loyalty. Improved operational strategies lead to better service quality, which in turn boosts consumer loyalty. Additionally, service quality plays a crucial mediating role in the relationship between operational strategies and patient loyalty.Conclusion: Satisfied patients are more likely to return, contributing to increased revenue and sustainability for hospitals.Original/Value: This research innovatively links operational strategies to patient loyalty in private hospitals, demonstrating how service quality mediates this relationship and drives revenue growth and business sustainability. Keywords: operational strategies, service quality, patient loyalty, patient satisfaction, company revenue